An investigation of Li2TiO3–coke composite anode material for Li-ion batteries. Issue 31 (5th June 2019) - Liu, Youlin; Li, Wensheng; Zhou, Xiaoping
Abstract : Anode material Li2 TiO3 –coke was prepared and tested for lithium-ion batteries. The as-prepared material exhibits excellent cycling stability and outstanding rate performance. Abstract : Anode material Li2 TiO3 –coke was prepared and tested for lithium-ion batteries. The as-prepared material exhibits excellent cycling stability and outstanding rate performance. Charge/discharge capacities of 266 mA h g −1 at 0.100 A g −1 and 200 mA h g −1 at 1.000 A g −1 are reached for Li2 TiO3 –coke. A cycling life-time test shows that Li2 TiO3 –coke gives a specific capacity of 264 mA h g −1 at 0.300 A g −1 and a capacity retention of 92% after 1000 cycles of charge/discharge.